Bank Credit and Economic Growth: Evidence from OIC Countries - Rusydiana, Aam Slamet; Ikhwan, Ihsanul (SMART Insight, 2023)
This study aims to explore the impact of bank credit along with three other independent variables, namely population, employment, and inflation, on economic growth in 55 Organization of Islamic Cooperation (OIC) member countries. The data used is annual panel data from 2010 to 2021, obtained from SESRIC OIC. The analysis method applied in this study is static panel data regression. The results show that each independent variable, such as population, employment, inflation, and total bank credit, has a significant effect both simultaneously and partially on the economic growth variable (GDP). Bank credit facilitates the efficient allocation of resources from savers to borrowers who have productive investment opportunities, thereby promoting economic growth. Second, banks act as an important channel in the transmission of monetary policy by providing financial intermediation, receiving and utilizing large amounts of public funds, and creating money supply. Third, bank credit expansion is associated with higher economic growth across industries, encouraging tangible investment but not intangible investment in more debt-dependent industries.